Herpesvirus Infections and Risk of Frailty and Mortality in Older Women: Women's Health and Aging Studies. Issue 5 (30th April 2016) - Wang, George C.; Han, Christina; Detrick, Barbara; Casolaro, Vincenzo; Levine, David M.; Fried, Linda P.; Walston, Jeremy D.
Abstract : Objectives: To examine the relationship between herpesvirus infections and mortality and incident frailty risks in community‐dwelling older women. Design: Nested prospective cohort study. Setting: Women's Health and Aging Studies I and II. Participants: Community‐dwelling older women aged 70 to 79 (n = 633). Measurements: Baseline serum antibody (immunoglobulin G) levels against four herpesviruses (herpes simplex virus types 1 (HSV‐1) and 2 (HSV‐2), varicella‐zoster virus (VZV), 7 Epstein‐Barr virus (EBV)), 3‐year incident frailty rates, and 5‐year mortality. Results: Women seropositive for HSV‐1 and HSV‐2, but not VZV and EBV, had higher risk of 3‐year incident frailty (HSV‐1: hazard ratio (HR) = 1.90, 95% confidence interval (CI) = 0.96–3.74; HSV‐2: HR = 2.10, 95% CI = 1.05–4.37) and 5‐year mortality (HR = 1.73, 95% CI = 0.93–3.20; HR = 1.80, 95% CI = 0.94–3.44, respectively) than seronegative women. Incremental increases in serum HSV‐1 and HSV‐2 antibody levels were associated with incrementally higher risks of incident frailty and mortality. After adjustment for potential confounders, only higher serum HSV‐2 antibody level was independently predictive of higher risk of mortality in older women (for each unit increase in antibody index, HR = 1.47, 95% CI = 1.05–2.07). Conclusion: HSV‐1 and HSV‐2 antibody levels are not independently associated with risk of incident frailty in older women. Only HSV‐2 antibody level is independently predictive of 5‐year mortality risk, with each incremental increase in the antibody level adding further risk.